Effect of Feeding Different Levels of Escherichia Coli Phytase and Buttiauxella Phytase on the Growth and Digestibility in Broiler - Bashir Ahmad, Rani Abro, Abdul Kabir, Bushra Rehman, Faryal Khattak, Hamid Ali Khan, Faiza Rashid, Muhammad Jawad Ullah, Muhammad Shadman, Mishal Bibi, Rizwan Ullah, Zeeshan Ahmed, Shubana Hayat, Junaid Ahmad, (Pakistan Journal of Medical & Health Sciences, 2022)
The effect of feeding different levels of bacterial phytase enzymes on the growth performance of broiler was examined using 250 Hubbard broilers, kept at the Poultry Experimental Station, Sindh Agriculture University Tandojam. The products of bacterial phytase enzymes were incorporated in the basal ration at different levels consisted of 0mg/kg (control), 50 mg/kg (group B), 100 mg/kg (group C) E. coli phytase and 50 mg/kg (group D), 100 mg/kg (group E) Buttiauxella spp. phytase. The birds were studied for live body weight, feed and water intake, feed conversion efficiency, carcass weight, dressing percentage, weight of internal edible and non-edible parts, digestibility and economics. The difference in live body weight among treatment and control group was significant (P<0.05). The significantly higher live body weight (2160.00g/bird) was observed in group E (fed 100mg/kg Buttiauxella phytase) and lower (2060g/bird) in group A (control). The effect of treatment on feed and water intake was significant (P<0.05), Feed (3800.00g/bird) and water (3800.00 ml/bird) intake was significantly higher in group A (control) than other treatment groups. Better feed conversion ratio (1.74) was noticed in group E followed by group C, B, D and A respectively. Carcass weight was significantly higher in group E (1350.60) and lower in control group (1219.71), the influence of feeding different sources and levels of bacterial phytase enzymes on dressing percentage was non-significant (P>0.05).Significant (P<0.05) difference was noted for heart weight among the groups and non-significant (P>0.05) difference were examined for gizzard, liver, spleen and proventiculus weight among the groups. The data showed that higher percentage of crude protein digestibility was recorded in group E (75%), then C (72%), B (71%), D (70.8%) and A (70%) respectively. Similarly M.E (kcal) was greater in group E (30.5%), then C (30%), B (29%), D (29%) and A (28.5%) respectively. The comparative net profit among all groups demonstrated that group E generated better net profit (48.70) followed by group C (47.88), B (41.50), D (40.30) and A (35.20) Rs/bird respectively.From the current findings, it was concluded that the supplementation of feed with 100mg/kg Buttiauxella spp phytase enzyme resulted in higher live body weight gain, better FCR and improved digestibility of nutrients. Keywords: phytase enzymes, Buttiauxella spp., E. coli, broiler,